LIVED IN EXPERIENCE OF WOMEN WITH BREAST CANCER - Samson, Blessy; Bhaskaran, Jayabharathi (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: Breast cancer is a kind of cancer that develops from breast cells. Breast cancer usually starts off in the inner lining of milk ducts or the lobules that supply them with milk. The objectives of the present study are to explore the lived in experience of women with breast cancer and to extrapolate the various dimensions of lived in experience of women with breast cancer. Methods: This qualitative study was conducted in different units of Metro Hospital and Cancer Institute, Delhi. Phenomenological approach was adopted for the study.The sample consisted of women with breast cancer who fulfilled the inclusion criteria. A total of 15 women with breast cancer were selected using non probability - purposive sampling technique. Structured questionnaire was used to assess the demographic variables of women with breast cancer.An interview schedule with open-ended questions was used to explore the lived in experience of women with breast cancer. The collected data from 15 women with breast cancer were analyzed using Collaizzi's seven - step methodological interpretation approach (analysis framework). Results: The investigator explored the lived in experience of women with breast cancer by conducting audio taped interview. Various dimensions such as physical dimension, psychological well-being, dealing with stigma, behavioral dimension, immaterial belief, human connectedness, and economical dimension were identified by the investigator. Under each dimension, sub-themes were formulated based on their lived-in experiences. Conclusion: Nurses working in the different health-care settings have the opportunity to explore the feelings of women with breast cancer and incorporating this knowledge while providing care to strengthen their coping mechanism, improve self-reliance and enhance quality of life. Keywords: Lived in experience, Women with breast cancer, Various dimensions.